Variabilitas Temperatur dan Salinitas Secara Musiman Di Perairan Selatan Jawa - Ima Nurmalia Permatasari (Jurnal Riset Kelautan Tropis (Journal Of Tropical Marine Research) (J-Tropimar), 2020)
The condition of the Java sea is strongly influenced by changes in surface oceanographic parameters and the atmosphere where surface currents originating from the east follow the winds that blow gradually throughout the year. Changes in currents caused by the influence of the wind cause the movement of the sea surface layer to generate horizontal mixing, which in turn will encourage a shift in the mass of water. The movement pattern of water masses will affect fluctuations in surface oceanographic parameters such as sea surface temperature, chlorophyll-a and salinity. Temperature and Salinity data are obtained from satellite image data which are then visualized using ODV (Ocean Data View) software with a vertical direction from the surface to near the seabed and then analyzed the vertical distribution of temperature, salinity and density representing the West, Transition I, East and Transition seasons. II. The sea surface temperature during the west season and transitional season I is higher than during the east season (August) and the transitional season 2. The salinity value of the sea surface in the west season and transitional season I is lower than during the east season and transitional season 2.